Effect of Replacing Fish Oil with Palm Oil on Growth Performance and Survival of Nile Tilapia (Oreochromis niloticus) - Ravi Bhatta; Sudarshan Poudel; Sapana Pandey; Shailesh Gurung; Arman Hossain Hossain (Airlangga University, 2025)
High cost and limited availability of fish oil (FO) in aquafeeds have prompted the search for alternative lipid sources. Palm oil (PO), a widely available and stable vegetable oil, may serve as a viable replacement in tilapia diets. This study investigated the effect of partially replacing fish oil (FO) with PO on the growth performance, feed utilisation, and survival of Nile tilapia cultured in cages. A 16-week feeding trial with four experimental diets was formulated by replacing FO with 0% (T0), 25% (T1), 50% (T2), and 75% (T3) PO. The diets were fed once daily to triplicate groups of 10 juvenile tilapia (7.75 ± 0.94 g), stocked into 12 cages (1 × 1 × 1 m³). Results indicate that there were no significant differences (p > 0.05) among treatments for final weight, final length, total biomass, specific growth rate (SGR), weight gain, survival rate, feed conversion ratio (FCR), and protein efficiency ratio (PER). The results suggest that PO can partially replace FO up to 50% in Nile tilapia diets without compromising growth, feed efficiency, or survival rate. This highlights PO’s potential as nutritionally viable lipid sources for sustainable aquafeed development.